A review of 91 canine and feline red‐bellied black snake (Pseudechis porphyriacus) envenomation cases and lessons for improved management. Issue 7 (23rd March 2022) - Wun, MK; Padula, AM; Greer, RM; Leister, EM
Abstract : Introduction: Most cases of red‐bellied black snake (RBBS) envenomation in dogs respond favourably to treatment comprising of tiger‐brown snake antivenom (TBAV), intravenous fluid therapy, analgesia and, if indicated, mechanical ventilation and/or blood transfusion. However, there remains a subset of patients who develop fatal complications despite intensive treatment and risk factors for these occurring remain unknown. Here we present a retrospective cross‐sectional survey of 91 canine and feline RBBS envenomation cases. Methods: Cases seen between June 2010 and June 2020 were retrieved from the databases of seven practices in South East and coastal Queensland. From the canine case population, logistic regression analysis was performed to assess the impact of potential risk factors at presentation on the likelihood of death. A final multivariable model was developed using a manual backwards elimination approach based on overall likelihood ratio tests and Wald chi‐square P‐values for each variable. Where model convergence failed due to quasi‐complete separation, Firth's penalised maximum likelihood method was implemented. Such separation may occur when an outcome is completely predicted by an explanatory variable in one group. Results: Of the 88 canine cases, 7 died (8.0%), all after prognosis‐based euthanasia. Of the three feline cases, one died after unsuccessful resuscitation following cardiopulmonary arrest. Compared to survivors, dogs that died were older, exhibited pigmenturia, received antivenom later and had a higher total plasma protein (TPP), activated clotting time (ACT) and lower packed cell volume (PCV) at presentation.